Development of rule-based mobile diagnostics system - Lee Hua, Leong, (Universiti Malaysia Sarawak (UNIMAS), 2015)
Mobile technologies are nowadays widely been used in many fields of professions due to its highly-efficient multitasking function and it is no exceptional to the psychology field. There are many mobile apps available in Google Play Store and Apple Store but those existing apps are only diagnosed for one particular cognitive disease. This project is intended to develop a mobile rule-based diagnosis system for several cognitive diseases for instance Post-traumatic stress disorder, autism spectrum disorder, bipolar disorder, obsessive compulsive disorder and social anxiety disorder. Reason for choosing these 5 cognitive diseases is because of these cognitive diseases are more common among the citizens in Malaysia. The purpose of this project is to gather the symptoms of these diseases and hence provide preliminary diagnosis to users through mobile application and yet raise the awareness of public towards these five cognitive diseases. Knowledge-based system framework is applied in developing the rule-based diagnosis mobile application and apparently, mobile application had developed by using Corona SDK. VisiRule software was used in generating valid and semantical rule-based system for this mobile application.